Work Experience, Competence, and Motivation are Significant Predictors of Employee Performance - Ratna Dewi (Jurnal Economic Resource, 2021)
This study aims to investigate the effect of employee motivation, competence, and job experience on employee performance. This study examines 43 public officials in the Makassar City Public Works Service's Regional Technical Implementation Unit (UPTD) Workshop. Primary data sources include observations and questionnaires, as well as documentation (secondary). The data analysis process included descriptive analysis, instrument validation (validity and reliability), classical assumption testing (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, and hypothesis testing (partial test, test simultaneously, and the coefficient of determination test). The findings indicated that motivation, competence, and work experience had a favorable effect on employee performance, with competency being the most influential variable. Employee performance improvement is impossible to isolate from the influence of characteristics such as motivation, competence, and work experience. Employee performance will also improve if motivation, competence, and work experience are enhanced additionally if the Makassar City Public Works Service's UPTD Workshop places a higher premium on employee expertise. This is because competency has a strong correlation with performance.